Estrategias pedagógicas para desarrollar la inteligencia emocional en los niños de primer año de educación básica de la escuela “Montevideo” del cantón Buena Fe, provincia de los Ríos. - Moreira Bravo, Jennifer Johanna (2017)
The main objective of this thesis is the implementation of Pedagogical Strategies to develop Emotional Intelligence in the elementary school children of the "Montevideo" School of Canton Buena Fe, Province of Los Ríos. For this purpose, it was based on an analysis of the shortcomings that children have in acquiring these shortcomings in emotional intelligence, this research puts a lot of interest in the subject so that the students can develop an excellent emotional intelligence being not only necessary the school but also in the activities of their daily lives, in order to obtain the data about the problem, a survey was conducted at the institution, aimed at teachers and students who expressed their realities, and the results obtained from the bibliographic review allowed for the elaboration of a proposed as a methodological tool for pre-school teachers